Nitrogen fertilization of common bean grown under no-tillage system after several cover crops - Silveira, Pedro Marques da; Braz, Antônio Joaquim Braga Pereira; Kliemann, Huberto José; Zimmermann, Francisco José Pfeilsticker (Pesquisa Agropecuaria Brasileira, 2005)
Nitrogen is an essential nutrient to common bean and its shortage is observed in almost all types of soils. The objective of this work was to evaluate the performance of irrigated common bean grown under no-tillage in succession to different cover crops and in relation to nitrogen topdressing fertilization in a Dystrophic Red Latosol (Typic Hapludox). The treatments were seven cover crops: Brachiaria brizantha cv. Marandu, B. brizantha associated with corn (Zea mays L.), pigeon pea (Cajanus cajan L. Millisp), millet (Pennisetum glaucum L. R. Br.), Panicum maximum cv. Mombaça, sorghum (Sorghum bicolor L. Moench) and Stylosanthes guianensis cv. Mineirão. The bean crop (cv. Perola) was seeded on the cover crop and 0, 30, 60, and 120 kg ha-1 of N (urea) were topdressed. The cover crops affected the common bean grain yield. The highest grain yields were attained on millet and pigeon pea mulches. The common bean grain yield showed response to nitrogen topdressing fertilization on all cover crops. The response was quadratic on millet and pigeon pea mulches and linear on the other cover crops.
Keywords: Phaseolus vulgaris; grass; leguminous; nitrogen; topdressing fertilization